Sosa’s Virtue Epistemology - Jonathan L. Kvanvig (Crítica)
Ernest Sosa’s latest epistemology remains a version of virtue epistemology, and I argue here that it faces two central problems, pressing a point I have made elsewhere, that virtue epistemology does not present a complete answer to the problem of the value of knowledge. I will press this point regarding the nature of knowledge through variations on two standard Gettier examples here. The first is the Fake Barn case and the second is the Tom Grabit case. I will argue that Sosa’s latest virtue epistemology fails to handle either case acceptably, and that as a result, cannot explain the value that knowledge has over that of the sum of any of its proper subparts.